Issues in the Establishment of Asset Management Companies - Ingves, Stefan; He, Dong.; Seelig, Steven (Washington, D.C. : International Monetary Fund, 2004)
This paper discusses the role of asset management companies (AMCs) in facilitating bank restructuring and specifies some policy lessons learned from international experience. The paper concludes that there is no single optimal solution but a combination of strategies that will vary from bank to bank and country to country. There are, however, common factors that contribute to the success of an AMC and these include the legal environment, leadership, independence, incentives, and commercial orientation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet